If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -11 + -2x = 39 Reorder the terms: -11 + X + -2x = 39 Solving -11 + X + -2x = 39 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '11' to each side of the equation. -11 + X + 11 + -2x = 39 + 11 Reorder the terms: -11 + 11 + X + -2x = 39 + 11 Combine like terms: -11 + 11 = 0 0 + X + -2x = 39 + 11 X + -2x = 39 + 11 Combine like terms: 39 + 11 = 50 X + -2x = 50 Add '2x' to each side of the equation. X + -2x + 2x = 50 + 2x Combine like terms: -2x + 2x = 0 X + 0 = 50 + 2x X = 50 + 2x Simplifying X = 50 + 2x
| 9q=8q-5 | | 12p=10p+4 | | 8x^5-8x^3+2x-1=0 | | 7.625x=2380 | | 5x-29=15x-61 | | 11y+8=6y+48 | | (x-5)2=7 | | -8(4x-2)=-112 | | (x+3)2=10 | | 0.5x^2-8=0 | | -3p+4(2-3p)=5 | | 4x^5+4x^4-9x^3-11x^2+x+3=0 | | 6x-9=-15x-9 | | 2x^2+x-150=0 | | 7(x+2(x-1))=3x | | 1x+4=15 | | 3x+0.28x=-8.82 | | 4x^2+29x+7=0 | | A=-4(8x-3)+6(-5x+3) | | =X^2-1 | | 6a^5+61a^3b^2+10ab^4=0 | | m+(2m+5.2)=41.8 | | 2x+2(2x-42)=228 | | -5+95x-90x^2=0 | | h=rt-256t | | -5x^2+14x+3=0 | | 2x^2+x-45=0 | | 81p^4-36p^3+4p^2=0 | | -15x^2+46x-35=0 | | 9x-14*5x+38= | | 10x^2=-21x+10 | | 7a^3b^3-63ab^3=0 |